THE IMPACT OF USING INSTAGRAM FOR INCREASING VOCABULARY AND LISTENING SKILL - Retno Widia Agustin; Mutiara Ayu (fsip.teknokrat.ac.id, 2021)
Currently studying does not have to use books. There are many media besides books that can be a place for us to increase our knowledge. At this time the world of technology is progressing rapidly as one of the needs of every human being. Smart phone, becoming the most commonly used technology in daily life, is no longer a luxury item. Moreover, the existence of various applications on smart phones makes it easier for us to find information anytime and anywhere. One of the applications found on smart phones that many people enjoy to use is Instagram. Instagram is a social media that can share various information such as photos and videos. There are several Instagram accounts where they share information about English lesson such as sharing photos using English captions and sharing long-duration videos such as IGTV using English, and not infrequently some accounts make teaching videos like in class using markers and whiteboards that will make us understand English more easily and interestingly and we also can increase our vocabulary by seeing the caption or watching video.